Comparison of plasma and salivary meteorin-like protein levels in patients with newly diagnosed Type-2 diabetes and treated with metformin - Kara, K. Tuncer; Kizil, M.; Cakmak, E.; Yildirim, T. T.; Kilinc, F.; Kuloglu, T.; Gozel, N. (Verduci Publisher, 2022)
OBJECTIVE: The present study compares the plasma and salivary Metrnl levels of patients newly diagnosed with type-2 dia-betes who were treated with metformin for three months with those of a healthy volunteer group and immunohistochemically analyzes Metrnl in salivary glands.PATIENTS AND METHODS: 30 healthy vol-unteers and 30 newly diagnosed type-2 diabetes patients were included in the study. The newly di-agnosed diabetes patients were treated with met-formin for three months, and the plasma and sal-ivary metformin levels of both groups were mea-sured at baseline and after the three months of metformin treatment in the patient group. Plas-ma HbA1c, low-density lipoprotein (LDL-C) and Triglyceride (TG) values of all groups were also measured at baseline following three months of metformin treatment. Biopsies were taken from the parotid and submandibular glands and im-munohistochemical staining was performed to show Metrnl immunoreactivity.RESULTS: Plasma Metrnl, HbA1c, LDL-C and TG levels were higher in the newly diagnosed di-abetes group than in the other group, and sali-vary Metrnl levels were higher than in the con-trol group after three months of metrformin treat-ment. An examination of the immunohistochemi-cal staining of salivary gland biopsies under light microscope revealed Metrnl immunoreactivity in the intralobular and interlobular ducts of the pa-rotid gland, while Metrnl immunoreactivity was observed in the acinar cells in the intralobular striated duct and interlobular ducts in the sub -mandibular gland.CONCLUSIONS: Plasma Metrnl, HbA1c, LDL-C and TG levels were higher in the new-ly diagnosed diabetes group than in the other group. Metrnl immunoreactivity was detected in the parotid and submandibular glands. The rela-tionship between Metrnl and DM should be inves-tigated in larger groups.
Keywords: Metrnl; Diabetes mellitus; Saliva Metrnl; Immunohisto-chemistry; Metformin